METHODOLOGICAL APPROACHES OF TEACHING SYNTACTIC VARIATIONS IN ENGLISH LANGUAGE: METHODOLOGICAL APPROACHES OF TEACHING SYNTACTIC VARIATIONS IN ENGLISH LANGUAGE - Aymanova, Shiyrinay (Журнал иностранных языков и лингвистики, 2025)
Language is a dynamic and intricate system that allows us multiple ways of expressing the same idea. One fascinating aspect of linguistic variation is syntactic synonymy, a phenomenon in which different syntactic structures convey the same or nearly the same meaning. Currently, there is no universally recognized theory of syntactic synonymy in Russian, foreign, or Uzbek linguistics and a condition that causes variability in language is syntactic synonymy. Syntactic variability allows language learners to construct sentences in multiple ways, promoting a deeper understanding of grammar, meaning, and nuances in the target language[1].The concept of variation is relatively broad and relates to various fields, and it can be seen that it has its own essence not only in the general socio-political or linguistic sphere, but also in the field of exact sciences. The study of syntax variability was analyzed by world linguists, N. Chomsky,[2] V.V. Vinogradov,[3] in their works, expressed their views on syntactic synonymy. According to Ellis [4], syntactic variability is essential for achieving fluency as it allows learners to adapt their language use to different contexts, settings, and communicative goals.